Inhibitor Formation in Congenital Hemophilia A: an Immunological Perspective - Delignat, Sandrine; Rayes, Julie; Russick, Jules; Kaveri, Srinivas V.; Lacroix-Desmazes, Sebastien; The ABIRISK consortium (Seminars in Thrombosis and Hemostasis, 2018)
The immunogenicity of therapeutic factor VIII (FVIII) in patients with hemophilia A has been puzzling scientific and clinical communities for more than 3 decades. Indeed, the development of inhibitory antibodies to FVIII remains a major clinical challenge and is associated with enormous societal costs. Thus, the reasons for which a presumably innocuous, short-lived, intravenously administered glycoprotein triggers such a deleterious, long-lasting neutralizing immune response is an enigma. This review does not pretend to bring an answer to this challenging question. It will however summarize the latest findings regarding the molecular interactions at play in the recognition of FVIII by the immune cells, the validity of the proposed risk factors for FVIII alloimmunization, and the different solutions that allow induction of FVIII-specific tolerance in preclinical models of hemophilia A.
Keywords: hemophilia A; factor VIII; immunogenicity